Profile of newborns submitted to therapeutic hypothermia in a private maternity hospital in Aracaju-Sergipe (Research, Society and Development, 2023)
Introduction: Hypoxic-Ischemic Encephalopathy (HIE) is the main neurological syndrome that occurs in Newborns (NB) subject to asphyxia. Globally, responsible for more than 1 million deaths per year. Therapeutic Hypothermia (TH) is currently the only approved neuroprotective treatment for patients with HIE. Objective: To describe the profile of newborns undergoing TH in a private maternity hospital in Aracaju-SE. Methods: Clinical, observational, descriptive and cross-sectional study carried out in a private maternity hospital in Aracaju-SE, where all newborns ≥ 35 weeks old who underwent TH from January 2019 to November 2020 were included. Results: Among hospitalized newborns (n=138), TH was indicated in 10.4% (n=14). The median gestational age of the newborns was 38 weeks, AGA (85.7%) and with adequate weight (85.7%), with no difference in relation to the method of delivery (vaginal in 57.1%). The majority had an Apgar score of £ 3  in the first minute (71.4%) and all required resuscitation maneuvers, intubation and sedation for the procedure. Only 14.3% of newborns started dieting before 48 hours. All newborns had some type of complication during the hypothermia period. Conclusion: The study showed that the majority of newborns undergoing TH were classified as low risk for complications according to the classification of gestational age at birth, birth weight and weight for gestational age. No difference was found in relation to the mode of delivery. The start of enteral feeding was late. Although complications were common, none of the patients died.